An Ontology-Based Contextual Knowledge Representation for Semantic Image Segmentation - Sreedhar, T; Sathappan, S (International Journal of Computer Sciences and Engineering, 2019)
Contextual Hierarchical Model (CHM) was a semantic image segmentation model which learned contextual information in a hierarchical framework. A Logistic Disjunctive Normal Networks (LDNN) classifier was used in each hierarchy level of CHM for semantic image segmentation. The class average accuracy of CHM may be affected due to the absence of global constraint. So, different Conditional Random Field (CRF) models were introduced to define global constraints through energy functions on a discrete random field. The efficiency of CHM based semantic image segmentation was greatly depended on the performance of LDNN. The performance of LDNN was enhanced by using a proximal gradient which minimizes the quadratic error of LDNN with fast convergence rate. Moreover, a Grey Wolf Optimization (GWO) algorithm was introduced to optimize the user specified weight and bias terms of LDNN which reduce the time complexity of LDNN. In this paper, CHM based semantic image segmentation is further improved by using ontology-based contextual knowledge representation in CHM. The ontology-based contextual knowledge representation constructs a relation based on taxonomic relations. In order to tackle the complex types of relations in images, a fuzzification is introduced in the ontology which is used to define the semantic relation between the concepts more effectively. Based on the fuzzified taxonomic relation, a relation is constructed which is given as additional input to the CHM for semantic image segmentation. The ontological taxonomic knowledge representation adjusts the segmentation results of CHM based on taxonomic relations. The experimental results show that the proposed Ontology-based contextual knowledge representation with CHM- Higher order Hierarchical CRF-Improved Optimized LDNN (OCHM-HHCRF-IOLDNN) has better performance in terms of class accuracy, pixel accuracy, F-measure and G-mean than the other method.